Evaluating Training Need for Epidemic Control in Three Metropolitans: Implications for COVID-19 Preparedness in Vietnam - Nguyen, Diep Ngoc; Le, Huong Thi; Thai, Phong Khanh; Le, Xuan Thi Thanh; Hoang, Men Thi; Vu, Linh Gia; Do, Toan Thi Thanh; Do, Khanh Nam; Vu, Giap Van; Nguyen, Tu Huu; Le, Thanh Tuan; Tran, Trung Dinh; et al. (Frontiers in Public Health, 2020)
Upon the outbreak of the COVID-19 pandemic, countries worldwide face a critical shortage of human resources in the health sector. Medical students are potential task force with the capability to support the stretched health sector. This study aims to evaluate their training need for epidemic control in order to employ them effectively. A cross-sectional study was conducted using a web-based survey from December 2019 to February 2020. There were 5786 observations collected using snowball sampling technique. Logistic regression was applied to identify factors associated with training participation in epidemic prevention and disaster prevention. Multiple Poisson regression model was constructed to examine factors associated with the number of times they participated in sanitation training and disaster prevention activities in the previous 12 months. Sanitation and health education communication activities had the highest proportion of participants, with 76.5% and 38.4%, followed by examining and treating diseases in the community (13.4%). Those who participated in community activities had a higher number of times participated in epidemic sanitation training and involved in disaster prevention. This study informed the need for training programs to prepare medical students for COVID-19 epidemic responses. Training curriculum should include both theoretical approaches and contextual approaches to achieve efficient epidemic control.